2013
DOI: 10.1016/j.jdent.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of a dentifrice containing 1.5% arginine and 1450 ppm fluoride to a dentifrice containing 1450 ppm fluoride alone in the management of early coronal caries as assessed using Quantitative Light-induced Fluorescence

Abstract: A new dentifrice containing 1.5% arginine, an insoluble calcium compound, and 1450 ppm fluoride, as sodium monofluorophosphate, provided statistically significant superior efficacy in arresting and reversing active coronal caries lesions in children than brushing with a matched positive control dentifrice containing fluoride alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
1
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 12 publications
3
66
1
10
Order By: Relevance
“…This is consistent with studies (no meta-analysis available) on enamel caries lesions in 7-to 14-y-old patients (Srisilapanan et al 2013;. Nonetheless, evidence level was graded as very low, and both studies included in this meta-analysis showed a high risk of bias, indicating that further high-qualitative clinical studies are warranted.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with studies (no meta-analysis available) on enamel caries lesions in 7-to 14-y-old patients (Srisilapanan et al 2013;. Nonetheless, evidence level was graded as very low, and both studies included in this meta-analysis showed a high risk of bias, indicating that further high-qualitative clinical studies are warranted.…”
Section: Discussionsupporting
confidence: 86%
“…For this reason, a silica-based sodium fluoride dentifrice was used as the control formulation in this study. Amongst the five clinical studies of 6 months duration and the in situ clinical studies which demonstrated the great promise of this technology, several have used calcium-based sodium monofluorophosphate toothpastes as matched controls and have also demonstrated superior anti-caries efficacy for the toothpaste containing 1.5% arginine [Cantore et al, 2013;Souza et al, 2013;Srisilapanan et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies, using quantitative light-induced fluorescence, have each shown that the new dentifrice containing 1.5% arginine, an insoluble calcium compound and 1,450 ppm F is significantly more effective in arresting and reversing coronal caries lesions in children than a dentifrice containing 1,450 ppm F alone [Srisilapanan et al, 2013;Yin et al, 2013a, b]. In one study, after 6 months of product use, improvements from baseline in ΔQ (lesion volume) were 50.7, 32.3 and 11.4% for the new arginine-containing dentifrice, a matched positive control dentifrice and a matched negative control dentifrice, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may act directly on plaque biofilm, maintaining plaque slightly supersaturated with respect to the tooth mineral Srisilapanan et al, 2013], but dental erosion occurs in the absence of plaque. In vitro studies on erosion showed the formation of a calcium-rich layer over demineralized enamel [Rege et al, 2014], where it is thought that arginine modifies the surface charge of enamel, heightening the affinity of calcium carbonate for the tooth surface [Rege et al, 2014].…”
Section: Amino Acids Peptides Proteins or Polymers Products Containmentioning
confidence: 99%